Network Positioning through Manufacturing Services - Lessons from the Contract Manufacturing Industry - Esa Viitamo; Seppo Luoto; Timo Seppälä (The Research Institute of the Finnish Economy (ETLA), 2016)
Through early adoption of new production technologies and service-based rivalry on the outsourcing customers, contract manufacturers integrate and enhance the efficiency of global supply networks. These influences evolve differently, however, depending on the network strategies and the competences of the contract manufacturing firms. Based on the recent findings in contract manufacturing this paper challenges and supplement the mainstream of servitization literature. In our focus the essence of servitization is not the shift to, or the specific requirements of running service business. We conclude that servitization appears more as an outcome when the firm aims for higher profitability through repositioning downstream in the industry value networks. Successful positioning and servitization is contingent on the customers' outsourcing strategies and the accumulated competences of the contract manufacturer. While services seems to be a prerequisite for the firms' survival in contract manufacturing business, their main purpose is to enhance customer value and retention rate in the long run. Our findings suggest that the way out of the `servitization trap' is a shift towards Original Design and Manufacturing concept where differentiated value adding modules can be integrated into replicable solutions for various customers and market segments.
Keywords: 330; Contract manufacturing; competence; servitization; value networks; outsourcing